Pengembangan dan Uji Kelayakan Media Pembelajaran 'Roket Terjun Islami' bagi Peserta Didik MI Kelas V - Mu'iz, Kaafin 'Abdul; Musyarofah, Nafisatul; Rahman, Ananta; Putranta, Himawan (Edification Journal : Pendidikan Agama Islam, 2024)
The aim of this study is to develop and evaluate the feasibility of the Roket Terjun Islami educational media for fifth-grade MI students, aiming to provide an engaging and effective alternative for teachers and enhance classroom learning quality. This research employs a Research and Development approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data were collected using questionnaires distributed to fellow students to assess the feasibility and effectiveness of the Roket Terjun Islami educational media. The questionnaire gathered information on design, content, and usability. The collected data were analyzed using descriptive quantitative analysis. Scores from each questionnaire item were summed to obtain the total score, compared to the maximum possible score to calculate the feasibility percentage. The feasibility assessment indicated the following results: the display aspect received 90.38% ("Very Feasible"), media material aspect achieved 95.00% ("Very Feasible"), learning aspect scored 92.85%, and content aspect received 87.85%, both "Very Feasible". These results demonstrate that the Roket Terjun Islami educational media is highly suitable for classroom use.